The impact of vocabulary assessments on quality of life: Insights from professionals on their application with students with disabilities. - Faisl Alqraini; Khalid Alasim; Abdulaziz Alqahtani (PLoS ONE)
Assessing vocabulary skills is a crucial aspect of educational interventions for students with disabilities, as it directly influences their academic progress, overall communication abilities, and quality of life. This study aims to explore professionals' perceptions regarding the vocabulary assessments used with students with disabilities. By gaining insights into their perspectives and experiences, we can improve the assessment process and enhance instructional practices, ultimately contributing to a better Quality of Life (QoL) for these students. Data were collected through a survey questionnaire completed by 375 professionals working in the field of special education. The findings indicate that professionals in the private sector express higher satisfaction levels and demonstrate better proficiency in applying vocabulary assessment tools compared to those in the public sector. Furthermore, the results reveal that professionals specializing in speech and language disorders report higher satisfaction levels compared to professionals in other specialized areas.